(untitled) (College of Basic Education Research Journal, 2025)
Mahmood Jandari stands among pioneers of short story writers locally, and nationally. He belongs to sixties generation who brought about turning point in short story. He is one of the few names that worked on experimentation and modernity in Iraqi narrative art, especially utilizing symbols of history, myths, wonders, color, and intersection of time, place, and characters in multiple forms. This research aimed to study historical symbol in short story of Mahmood Jandari. This research consists of an introduction and three sections. The introduction included defining concept of historical symbol. First section devoted to study historical symbol in story collection ( Years of Thirst), second studies historical symbol in his story collection (The Siege), while third section dealt with historical symbol in his story collection ( Terraces of the gods). Research adopted an analytical method of historical symbol in short story of Mahmood Jandari, according to objective analysis to demonstrate aesthetic value of narrative texts.